Cold acclimation and prospects for cold-resilient crops - Collin L. Juurakko (Elsevier, 2021)
Low-temperatures pose extreme challenges to crops causing significant economical impacts. Frosts are responsible for more than 30% of weather-related insured crop losses in some temperate climate jurisdictions, but are particularly devastating for small holdings and communities reliant on a bountiful harvest. Low-temperatures are also frequently accompanied by other abiotic and biotic stresses, including pathogen attacks. Some pathogens have sub-zero temperature optima, while others leverage low-temperatures to promote freezing at high sub-zero temperatures by way of ice-nucleating proteins in order to access intracellular nutrients. To survive low-temperatures and the attendant risks, various plant species have evolved complex and intricate signaling networks, molecular mechanisms, and physiological changes, in addition to symbiotic relationships with microbiota. Enhancing low-temperature survival and pathogen-induced freezing tolerance in cold susceptible, agriculturally significant crops is an attractive area of research with immense translatable value to all aspects of society. This area of research will be particularly important in our near future as climate change increases the unpredictability of frosts, particularly in the spring and autumn. Against this backdrop, the world population continues to grow while arable land remains finite and wealth inequality exacerbates food poverty. In this review, we examine plant (i) low-temperature stress, (ii) cold acclimation responses, particularly in crops (iii) antifreeze proteins, and (iv) frost-associated pathogens. Lastly, we suggest integrated approaches to improve crop frost tolerance.